Museum Purbakala Bumiayu sebagai Media Pembelajaran Kontekstual Berbasis Religius di Sekolah Dasar - Arifin, Muh Luqman; Mukrodin; Pertiwi, Amelia Khana; Ida, Yuhdiyati Nur; Jinan, Tsalwa Diyaul (Dharmahita: Journal of Community Service and Development, 2025)
This community service activity aims to develop and implement a religious-based contextual learning model by utilizing local potential, namely the Bumiayu Archaeological Museum in Brebes Regency, Central Java, as a learning medium in elementary schools. The program was carried out through collaboration between the community service team of Peradaban University and SD Islam Ta'allumul Huda Bumiayu, with a focus on developing learning modules and media entitled "Tracing Historical Traces at the Bumiayu Archaeological Museum." The approaches used include Contextual Teaching and Learning (CTL), experiential learning, and inquiry-based learning, which emphasize the active involvement of students in the process of exploration, observation, and reflection on Islamic values contained in museum artifacts. The results of the activity show that this learning model is able to simultaneously improve students' understanding of historical concepts and Islamic values. A total of 90% of students demonstrated good reflective skills in relating archaeological findings to Islamic teachings, while teachers stated that the developed modules were very helpful in integrating local potential into thematic learning. In addition, positive responses from the school reinforced plans to develop this program as part of the Pancasila-Based Islamic Student Profile and the School Activator Program.